ANALISIS VOLATILITAS HARGA MINYAK DUNIA TERHADAP PURCHASING POWER SEBAGAI DAMPAK RESESI EKONOMI - Mutia Nur Inayah (Politeknik Bisnis Indonesia, 2023)
This study examines how the Volatility of World Oil Prices, Inflation, Interest Rates and Exchange Rates affect Public Purchasing Power (Purchase Power Parity) in Indonesia. The data used is data from 2012-2021. Quantitative data, or data in the form of numbers, is used in the quantitative descriptive methodology of this study. This study uses the calculation model of the ARCH method and the Error Correction Mechanism (ECM) model with Eviews 9. The results based on volatility analysis show a value of α1 + β1 < 1 0.50. This means that the volatility of oil prices is low. The r value is 0.994690 or 99.46%, meaning that there is a relationship between the independent variables World Oil Price Volatility, Inflation, Interest Rates and Exchange Rates with the dependent variable Purchase Power Parity has a strong relationship because it is close to 100%. Keywords: Purchasing Power Parity, Volatility, Inflation, Interest Rates, Exchange Rates